Aktivitas Bisnis dalam Tinjauan Aspek Hukum Perjanjian - Amelia, Farissa; Nazaruddin, Nazaruddin (Al-Hiwalah: Journal of Sharia Economic Law, 2022)
The development of the business world, especially trade in Indonesia, seems to be dominated by trade in goods which is the result of cooperation between Indonesian entrepreneurs and foreign entrepreneurs, and between Indonesian entrepreneurs and Indonesian entrepreneurs. Agreement as a private legal relationship that exists between parties who have entered into an agreement, on objects that have been agreed upon as a form of fulfillment of rights and obligations, after the creation of an agreement.